Análise da reprodutibilidade de parâmetros no domínio da frequência do sinal EMG utilizados na caracterização da fadiga muscular localizada - da Silva, Cristiano Rocha [UNESP]; Geres, Beatriz Sanches [UNESP]; Kuriki, Heloyse Uliam [UNESP]; Negrao Filho, Ruben de Faria [UNESP]; Alves, Neri [UNESP]; de Azevedo, Fabio Micolis [UNESP] (Universidade Estadual Paulista (Unesp), Instituto de Biociências, 2012)
The aim of this study was to analyze the reproducibility of the electromyography signal's parameters (EMG) in the frequency domain used in the characterization of localized muscle fatigue. Fifteen male subjects underwent a fatigue test based on isometric knee extension, being held at three different times at intervals of seven days. To assess the reproducibility of data between the tests we calculated the correlation coefficient (ICC) for the median frequency (MF) in total exercise time (MFT), MF obtained for every 10% of exercise time (MF10%) and the powers of the frequency bands obtained by dividing the power spectrum at windows of 20 Hz. The results showed: (1) excellent reproducibility for MFT, (2) good reproducibility for MF10%, and (3) greater variation in the signal EMG bands from 20 to 120 Hz, especially at the bands of 20-40 Hz and 40-60 Hz, which showed greater sensitivity to the process of muscle fatigue. We conclude that the MF is a variable that shows good reproducibility and that the fragmented analysis of the power spectrum, by means of frequency bands, showed that significant variations occur in the EMG signal during the installation of the fatigue process, having potential to become a new method for the characterization of localized muscle fatigue.

O objetivo deste estudo foi analisar a reprodutibilidade de parâmetros no domínio da frequência do sinal eletromiográfico (EMG) utilizados na caracterização da fadiga muscular localizada. Quinze sujeitos do sexo masculino foram submetidos a um teste de fadiga baseado na extensão isométrica de joelho, sendo realizados em três momentos distintos com intervalos de sete dias. Para avaliar a reprodutibilidade dos dados entres os testes calculou-se o coeficiente de correlação intraclasse (CCI) para a frequência mediana (Fmed) no tempo total de exercício (FmedT), para a Fmed obtida a cada 10% do tempo de exercício (Fmed10%) e para as potências das bandas de frequência, obtidas da divisão do espectro de potência a cada 20 Hz. Os resultados demonstraram: (1) boa reprodutibilidade para a FmedT; (2) boa reprodutibilidade para a Fmed10%; e (3) maior variação no sinal EMG nas bandas de 20 a 120 Hz, no qual se destacam as bandas de 20-40 Hz e de 40-60 Hz, demonstrando maior sensibilidade ao processo de fadiga muscular. Conclui-se que a Fmed é uma variável que apresenta boa reprodutibilidade e que a análise fragmentada do espectro de potência, por meio das bandas de frequência, demonstrou-se sensível as variações que ocorrem no sinal EMG durante a instalação do processo de fadiga, tendo potencial para se tornar um novo método para a caracterização da fadiga muscular localizada.
Analysis of reliability of EMG signal frequency domain parameters used in the characterization of localized muscle fatigue
Keywords: Electromyography; Fatigue; Reproducibility of results; Biomechanics; Quadriceps muscle; Median frequency